Radiotherapy for tumors of the stomach and gastroesophageal junction - a review of its role in multimodal therapy - Bürgy, Daniel; Lohr, Frank; Baack, Tobias; Siebenlist, Kerstin; Haneder, Stefan; Michaely, Henrik J. M.; Wenz, Frederik; Boda-Heggemann, Judit (Radiation oncology, 2012)
There is broad consensus on surgical resection being the backbone of curative therapy of gastric- and gastroesophageal junction carcinoma. Nevertheless, details on therapeutic approaches in addition to surgery, such as chemotherapy, radiotherapy or radiochemotherapy are discussed controversially; especially whether external beam radiotherapy should be applied in addition to chemotherapy and surgery is debated in both entities and differs widely between regions and centers. Early landmark trials such as the Intergroup-0116 and the MAGIC trial must be interpreted in the context of potentially insufficient lymph node resection. Despite shortcomings of both trials, benefits on overall survival by radiochemotherapy and adjuvant chemotherapy were confirmed in populations of D2-resected gastric cancer patients by Asian trials.